Fig fruit growth and quality development as affected by phloem stress - Abms, H.; Boyce, A.N. (2009)
Fig fruit set, growth and yield, weight and maturity index as influenced by phloem stress (represented by partial bark ring) were studied. The treatments were namely control (unringed), 1-shape partial ring (I-SPR), X-shape partial ring (X-SPR) and S-shape partial ring (S-SPR) at pre harvest stage. Phloem stress was represented by partial bark ringing. The percent flower bud and fruit set were greater in S-SPR treated than in other treated branches. However, the result showed that all three treated branches had significantly higher percentage of flower bud and fruit set than that of the control one. Fruit length and diameter were higher in I-SPR, S-SPR, X-SPR treated branches than in control (un-ringed). Fruit number per bunch was lower in treated branches than in control branches. On the contrary, bunch weight, per fruit weight, soluble solids content and maturity index were greater in I-SPR, S-SPR, X-SPR treated branches than in control (un-ringed) branches. The result showed that phloem stress represented by partial ringing as dwarfing component was a useful practice for fig fruit growth and quality development.